Pengaruh Intellectual Capital, Company Size, dan Capital Structure Terhadap Kinerja Keuangan pada Perusahaan Properti and Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2023 - Yuwandono, Rr Jihan Faadhilah; Trihastuti, Rr Adiati (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to analyze the effect of intellectual capital, company size, and capital structure on the financial performance of Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2023 period. Financial performance is measured using three ratios, namely Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The research sample consisted of 43 companies selected using purposive sampling method. The analysis methods used in this research are descriptive test, model feasibility test, multiple linear regression, classical assumption test and hypothesis testing. The results showed that intellectual capital has a positive and significant effect on the company's financial performance. Meanwhile, company size has no significant effect on financial performance. On the other hand, capital structure has a significant effect on NPM and ROE, but has no significant effect on ROA. These findings indicate the importance of intellectual capital management and capital structure in improving the financial performance of companies in the Property and Real Estate sector, although company size has no significant effect.